(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The study tends to identify the strategic partnership of both EU and NATO. As result, the research found that EU has many responsibilities based on its normative powers ambition than NATO which is militarily oriented organization. EU deals with mainly economic and social affairs without neglecting its security necessities, while NATO is very much concerned about the security perspectives. Furthermore, examining the historical background of both institutions in this particular study, the author found that the strategic partnership and their future plans are based on their mutual understanding during their meetings. So, having consensus before any decision is the strategic approach that is strengthening the cooperation between both institutions. Another angle that the author found out is that EU might be replaced by NATO for military operation in any time of need, due to the EU normative powers economic and social activities ambition in the international arena. In this paper, we describe the formatting guidelines for CIR Journal Submission.The entire paper must be in A4 size and Moderate margin